An analytic superfield formalism for tree superamplitudes in D=10 and D=11 - Igor Bandos (Journal of High Energy Physics, 2018)
Abstract Tree amplitudes of 10D supersymmetric Yang-Mills theory (SYM) and 11D supergravity (SUGRA) are collected in multi-particle counterparts of analytic on-shell superfields. These have essentially the same form as their chiral 4D counterparts describing N=4 $$ \mathcal{N}=4 $$ SYM and N=8 $$ \mathcal{N}=8 $$ SUGRA, but with components dependent on a different set of bosonic variables. These are the D=10 and D=11 spinor helicity variables, the set of which includes the spinor frame variable (Lorentz harmonics) and a scalar density, and generalized homogeneous coordinates of the coset SOD−2SOD−4⊗U1 $$ \frac{SO\left(D-2\right)}{SO\left(D-4\right)\otimes U(1)} $$ (internal harmonics). We present an especially convenient parametrization of the spinor harmonics (Lorentz covariant gauge fixed with the use of an auxiliary gauge symmetry) and use this to find (a gauge fixed version of) the 3-point tree superamplitudes of 10D SYM and 11D SUGRA which generalize the 4 dimensional anti-MHV superamplitudes.